The evolution of three decades of antiretroviral therapy: challenges, triumphs and the promise of the future. (February 2015) - Tseng, Alice; Seet, Jason; Phillips, Elizabeth J.
<x xml:space="preserve">Abstract</x> The evolution of human immunodeficiency virus (HIV) treatment has improved our understanding and management of complex pharmacological issues that have driven improved outcomes and quality of life of the HIV‐infected patient. These issues include adherence, long‐ and short‐term toxicities, pharmacoenhancement, pharmacogenomics, therapeutic drug monitoring, differential penetration of drugs into sanctuary sites, such as the central nervous system, genital tract and small bowel, and drug–drug and drug–food interactions related to cytochrome P450 drug‐metabolizing enzymes, uridine diphosphate glucuronyltransferases and drug transporters, to name a few. There is future promise, as an increased understanding of the immunopathogenesis of HIV and global public health initiatives are driving novel treatment approaches with goals to prevent, control and, ultimately, eradicate HIV.